Mobile school canteen food ordering system / Masurah Mohamad, Lathifah Alfat and Nurul Farah Dieana Madzli - Mohamad, Masurah; Alfat, Lathifah; Madzli, Nurul Farah Dieana (Universiti Teknologi MARA, Perak, 2021)
Food ordering has been familiar nowadays. Everyone is very concerned about time and the necessities of life such as food. The food ordering application helps people to get their food easily and save lots of time. Most of the existing food ordering applications only focused on registered restaurants or food providers based on the specific location. However, there is no special food ordering application that focused on food ordering for school students and canteen food provider in Malaysia. Even though many food ordering applications are available to be used, the most apparent drawback to food ordering applications is that students are unable to use them during breaks at the school. Due to this problem, a mobile application named as Mobile School Canteen Food Ordering System is proposed as an alternative to the school students in selecting and ordering the food offered by the school canteen food provider. In addition, with the implementation of collaborative filtering technique, this system offered one additional function that will recommend the user on healthy meal that the children should consume according to the provided criteria such as foods that contain allergens. This project will benefit many students especially in primary schools whereas 75% of the respondents have agreed that the system is effective in choosing foods easily, facilitate and save their time to get food during breaks.